Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1583/04-1432r.1
|View full text |Cite
|
Sign up to set email alerts
|

Preserved Pelvic Circulation After Stent-Graft Treatment of Complex Aortoiliac Artery Aneurysms:A New Approach

Abstract: By extending the distal aspect of the stent-graft into an IIA, bilateral CIA aneurysms can be excluded while preserving pelvic circulation on one side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 17 publications
0
30
0
3
Order By: Relevance
“…8 To increase the applicability of endovascular treatment in the presence of complex iliac aneurysms, different solutions aimed at preserving pelvic circulation have been proposed: surgical revascularization of the hypogastric artery prior to endovascular exclusion 9 , EIA-to-IIA retrograde endograft placement with contralateral aortomonoiliac stent-graft, 10 branched stent-grafts, [11][12] and antegrade stent-grafting of a bifurcated endograft into the IIA. 13,14 However, all these techniques have limited applicability, and the concomitant occlusion of one EIA further limits their use.…”
Section: Discussionmentioning
confidence: 99%
“…8 To increase the applicability of endovascular treatment in the presence of complex iliac aneurysms, different solutions aimed at preserving pelvic circulation have been proposed: surgical revascularization of the hypogastric artery prior to endovascular exclusion 9 , EIA-to-IIA retrograde endograft placement with contralateral aortomonoiliac stent-graft, 10 branched stent-grafts, [11][12] and antegrade stent-grafting of a bifurcated endograft into the IIA. 13,14 However, all these techniques have limited applicability, and the concomitant occlusion of one EIA further limits their use.…”
Section: Discussionmentioning
confidence: 99%
“…Various techniques have been described in the endovascular management of aortic aneurysms involving the CIA. Delle and colleagues described a method in which one limb of a bifurcated stent‐graft was extended to the external iliac artery (EIA), while the contralateral limb was deployed into the IIA and the contralateral blood flow to the EIA was restored via a femoro‐femoral cross‐over graft 9 . Alternatively, the IIA could be replanted to the EIA or revascularized by a surgical bypass from the EIA via a PTFE graft 10 .…”
Section: Discussionmentioning
confidence: 99%
“…The approach decreases the likelihood of a type II endoleak resulting from retrograde flow via the IIA and eliminates the need to construct an open extra‐anatomical bypass. However, it poses the potential of compromising pelvic circulation and several reports have suggested that up to 30% of patients developed buttock claudication after the procedure and a smaller proportion developed sexual dysfunction, transient urinary retention and bowel ischaemia 2,3,8,9,12 …”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Bilateral IIA embolization or occlusion may result in particularly severe morbidity, 5 and many strategies to preserve IIA flow have been suggested, including femoro-femoral bypass and surgical or endograft external-to-internal iliac revascularization. [7][8][9] Initial reports of short-term outcomes following the new technique of branched stent graft placement to ensure IIA perfusion have been favorable. 10,11 Recently, longer-term data has emerged regarding the exciting potential of this technique, with favorable reports of midterm outcomes.…”
Section: Introductionmentioning
confidence: 99%